(3MGTjI Ydi GdTeSjIs - (3ZjGK GdOjf efUhQ Hf eMeO Hf UOQ GdOjf GdOTJcj GdTjQGRj,J (B948 (3g` s
(3ChdgG (B:s
(3CMeO Gddg Ydi eG habfG ddJUOjb HeUOGb QSGdI TeSjI GdETQGb s
(3BNQgG (B:s
(3JeJ s
(3Vef eLehY , JQJjHgG (B: 4s
(3GdQSGdI GdCUdjI(B: (3GdQSGdI GdTeSjI ai GdbhGYO GdefWbjI ddcGJHis
(3HBNQgG JdNjU ddQSGdI ai GdeZGdWI ef hQbI (B62 (3Edi (B63s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B244s
Keywords: (3GdadSaI hGdefWbs